Trans–Abdominal Wall Traction as a Universal Solution to the Management of Giant Ventral Hernias. Issue 4 (April 2015) - Dennis, Andrew J.; Salabat, Reza; Kingsley, Samuel; Starr, Frederic; Joseph, Kimberly; Wiley, Dorion; Messer, Thomas; Poulakidas, Stathis; Nagy, Kimberly; Bokhari, Faran
Abstract : Background: Domain loss following damage-control laparotomy is a challenging problem many surgeons face. The authors recently developed trans–abdominal wall traction, which closed 100 percent of domain loss abdomens in the acute setting. They hypothesized that it can be used successfully in patients with chronic giant ventral defects. Methods: From 2008 to 2013, 44 patients with acute loss of domain and 10 with chronically giant ventral defects were enrolled in the open abdomen protocol with subsequent placement of the trans–abdominal wall traction device. Results: Patients' average age in the acute and chronic groups was 28.2 and 35.3 years and average body mass index was 26.4 and 32.4 kg/m 2, respectively. Ventral hernia size was reduced with the first trans–abdominal wall traction insertion from 610.5 cm 2 to 274.6 cm 2 in the acute setting and from 598 cm 2 to 236.9 cm 2 in the chronic setting. Average time from damage-control laparotomy to device insertion was 12.9 days in the acute group and more than 3 years in the chronic group. Lost domain was achieved with an average of less than 2.5 trans–abdominal wall traction tightenings, correlating to 9.2 and 8.2 days in the acute and chronic groups, respectively. Enterocutaneous fistula occurrence was 9 percent in the acute group and 0 percent in the chronic group. Conclusions: All patients were successfully closed after reestablishment of the lost domain. Trans–abdominal wall traction is an effective means of reestablishing abdominal domain and achieving primary abdominal wall closure in all patients with giant ventral defects, both acute and chronic. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.